Disrupting the third space through playfulness, mattering, and unbounded perspectives - Ian Fellows; Gill Gilbert; Leoarna Mathias; Sarah Parkes (Journal of Learning Development in Higher Education)
This paper explores the evolving landscape of higher education in the UK, emphasising the diversity of the student population and the ensuing challenges for traditional university frameworks. It is framed through the concept of ‘third space’ professionals – individuals who operate beyond the conventional academic and administrative divides – to address these challenges (Whitchurch, 2013). The authors use reflective narratives that are diffracted through each other to shed light on the complexity of functioning in this innovative space. Their experiences of working-class origins, transitions from other sectors, and mature student pathways, illustrate how diversity enriches their engagement with students and their contribution to the university environment. The narrative showcases how third space professionals are pivotal in enhancing student success and promoting a more inclusive and student-focused university culture. They challenge existing academic hierarchies and bureaucratic norms, fostering a more adaptable and responsive educational setting. The paper highlights four third space practitioners’ creative and strategic approaches to navigating and reforming university structures whilst facing institutional resistance and systemic hurdles. Through principles of disruption, ethical practice, playfulness, and boundary-crossing, third space professionals are depicted as agents of cultural change, advocating for broader recognition and expansion of their roles in the academic ecosystem. In conclusion, the authors argue for the vital importance of the third space in higher education innovation, where the unique backgrounds of professionals significantly impact university transformation.